Integrating Technology in PE: A Scoping Review of Drone Soccer as a Catalyst for Student Skill Development and Ethical Awareness - Frankie U Kei Wong; QiTing Zhou; Water Soi Po Wong (Journal of Educational Technology and Learning Creativity, 2026)
Purpose of the study: This study investigates drone soccer's potential as a pedagogical tool for integrating technology within physical education (PE). It bridges traditional athletics and STEM-oriented motor skills, exploring how this sport facilitates the dual-track development of technical proficiency and ethical responsibility in K-12 and higher education. Methodology: Guided by the updated PRISMA guidelines, this scoping review comprehensively synthesizes 35 key studies from multidisciplinary databases. It utilizes the I-TPACK and SAMR models to assess the depth of technology integration. Furthermore, reflexive thematic analysis (RTA) evaluates drone soccer's pedagogical and ethical efficacy across psychomotor, cognitive, and social-emotional domains. Main Findings: The analysis suggests that drone soccer functions as a significant catalyst for enhancing visual-motor integration (VMI), fine motor dexterity, and collaborative problem-solving. Beyond physical benefits, the sport provides a structured environment for instilling "technological ethics," promoting fair play, privacy awareness, and responsible tech usage. Applying the SAMR model reveals that drone soccer allows for a "redefinition" of PE activities, transforming conventional sports into high-level, interdisciplinary learning experiences that dissolve the boundaries between physical activity and digital engineering. Novelty/Originality of this study: This paper offers a pioneering perspective by positioning drone soccer at the intersection of competitive robotics and physical education. Unlike traditional technology integration studies that focus on exergaming or wearables, it uniquely identifies drone soccer as a holistic vehicle for both advanced motor skills and ethical consciousness, providing a validated theoretical roadmap for future technology-enhanced PE curricula.